Inclusion, characteristics, and outcomes of male and female participants in large international perioperative studies. (September 2022) - Leslie, Kate; Martin, Catherine; Myles, Paul S.; Devereaux, P.J.; Peyton, Philip J.; Story, David A.; Wijeysundera, Duminda N.; Cuthbertson, Brian H.; Short, Timothy G.; Corcoran, Tomás B.; Kasza, Jessica
Abstract: Background: We compared baseline characteristics and outcomes and evaluated the subgroup effects of randomised interventions by sex in males and females in large international perioperative trials. Methods: Nine randomised trials and two cohort studies recruiting adult patients, conducted between 1995 and 2020, were included. Baseline characteristics and outcomes common to six or more studies were evaluated. Regression models included terms for sex, study, and an interaction between the two. Comparing outcomes without adjustment for baseline characteristics represents the 'total effect' of sex on the outcome. Results: Of 54 626 participants, 58% were male and 42% were female. Females were less likely to have ASA physical status ≥3 (56% vs 64%), to smoke (15% vs 23%), have coronary artery disease (21% vs 32%), or undergo vascular surgery (10% vs 23%). The pooled incidence of death was 1.6% in females and 1.8% in males (risk ratio [RR] 0.92; 95% confidence interval [CI]: 0.81–1.05; P =0.20), of myocardial infarction was 4.2% vs 4.5% (RR 0.92; 95% CI: 0.81–1.03; P =0.10), of stroke was 0.5% vs 0.6% (RR 1.03; 95% CI: 0.79–1.35; P =0.81), and of surgical site infection was 8.6% vs 8.3% (RR 1.03; 95% CI: 0.79–1.35; P =0.70). Treatment effects of three interventions demonstrated statistically significant effect modification by sex. Conclusions: Females were in the minority in all included studies. They were healthier than males, but outcomes were comparable. Further research is needed to understand the reasons for this discrepancy. Clinical trial registration: International Registry of Meta-Research (UID: IRMR_000011; 5 January 2021).